Heterogeneous Nuclear Ribonucleoprotein A2/B1 Regulates the Self‐Renewal and Pluripotency of Human Embryonic Stem Cells Via the Control of the G1/S Transition. (December 2013) - Choi, Hong Seo; Lee, Hyun Min; Jang, Young‐Joo; Kim, Cheorl‐Ho; Ryu, Chun Jeih
<x xml:space="preserve">Abstract</x> Self‐renewal and pluripotency of human embryonic stem cells (hESCs) are a complex biological process for maintaining hESC stemness. However, the molecular mechanisms underlying these special properties of hESCs are not fully understood. Heterogeneous nuclear ribonucleoprotein A2/B1 (hnRNP A2/B1) is a multifunctional RNA‐binding protein whose expression is related to cell proliferation and carcinogenesis. In this study, we found that hnRNP A2/B1 expression was localized to undifferentiated hESCs and decreased upon differentiation of hESCs. hnRNP A2/B1 knockdown reduced the number of alkaline phosphatase‐positive colonies in hESCs and led to a decrease in the expression of pluripotency‐associated transcription factors OCT4, NANOG, and SOX2, indicating that hnRNP A2/B1 is essential for hESC self‐renewal and pluripotency. hnRNP A2/B1 knockdown increased the expression of gene markers associated with the early development of three germ layers, and promoted the process of epithelial‐mesenchymal transition, suggesting that hnRNP A2/B1 is required for maintaining the undifferentiated and epithelial phenotypes of hESCs. hnRNP A2/B1 knockdown inhibited hESC proliferation and induced cell cycle arrest in the G0/G1 phase before differentiation via degradation of cyclin D1, cyclin E, and Cdc25A. hnRNP A2/B1 knockdown increased p27 expression and induced phosphorylation of p53 and Chk1, suggesting that hnRNP A2/B1 also regulates the G1/S transition of hESC cell cycle through the control of p27 expression and p53 and Chk1 activity. Analysis of signaling molecules further revealed that hnRNP A2/B1 regulated hESC proliferation in a PI3K/Akt‐dependent manner. These findings provide for the first time mechanistic insights into how hnRNP A2/B1 regulates hESC self‐renewal and pluripotency. STEM Cells2013;31:2647–2658